2020
DOI: 10.1136/openhrt-2019-001183
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tricuspid regurgitation on postoperative outcomes after non-cardiac surgeries

Abstract: ObjectiveTricuspid regurgitation (TR) severity has known adverse implications, its impact on patients undergoing non-cardiac surgery (NCS) remains unclear. We sought to determine the impact of TR on patient outcomes after NCS.MethodsWe performed a retrospective cohort study in patients undergoing NCS. Outcomes in patients with moderate or severe TR were compared with no/trivial TR after adjusting for baseline characteristics and revised cardiac risk index (RCRI). The primary outcome was defined as 30-day morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Not all valvular pathologies are clinically significant; mild mitral or tricuspid valve diseases need only a change in lifestyle, according to the most recent guidelines [ 28 , 39 ]. Patients with moderate–severe tricuspid insufficiency had a greater risk of mortality and morbidity 1 month after surgery, not correlated with RCRI scores or ejection fraction [ 50 ]. Moreover, severe aortic stenosis is associated with a higher risk of MACEs at 1 month after surgery (18.8%), whether symptomatic or not; the risk of mortality due to MACE was similar if correlated with class I or II of RCRI score and increased only with an RCRI score > 2 [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not all valvular pathologies are clinically significant; mild mitral or tricuspid valve diseases need only a change in lifestyle, according to the most recent guidelines [ 28 , 39 ]. Patients with moderate–severe tricuspid insufficiency had a greater risk of mortality and morbidity 1 month after surgery, not correlated with RCRI scores or ejection fraction [ 50 ]. Moreover, severe aortic stenosis is associated with a higher risk of MACEs at 1 month after surgery (18.8%), whether symptomatic or not; the risk of mortality due to MACE was similar if correlated with class I or II of RCRI score and increased only with an RCRI score > 2 [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines are therefore not predicated on cumulative evidence [ 25 , 26 ]. Many recent studies have suggested that early surgery is better since it improves short- and long-term post-operative outcomes [ 27 , 28 , 29 ]. A prior study suggested that restoring normal life expectancy did not occur even in patients with NYHA class II symptoms [ 30 ], emphasizing the need for TR surgical management before heart failure symptoms develop [ 31 ].…”
Section: Tricuspid Valvementioning
confidence: 99%